English studies in an Afrikaans University* - Venter, J. A. (Koers, 1964)
University studies in English are a comparatively recent introduction at English universities. Cambridge, for instance, first established a Chair of English in 1911. The comparable dates for certain other subjects are as follows: Mechanics, 1875; Physics, 1871; Zoology, 1866. Cambridge was, in fact, the last of the senior British uni versities to establish a Chair of English. Edinburgh, ap parently, was the first, with its Chair of Belles-Lettres which was an off-shoot of the Department of Logic. The need for this Chair arose partly from the replacement of Latin as the medium of instruction by English. Nowa days one often finds that the practical study of English as a means of communication is rejected on traditional grounds as unacademic. It is rather disconcerting to find that for the first 135 years of its existence the oldest University Department of English devoted its energies at least partly to what we would call "Practical English.”